Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's analyze the nature of the functions step by step.
Given:
- [tex]\( f(x) \)[/tex] is an even function.
- [tex]\( g(x) \)[/tex] is an odd function.
We need to determine whether the following functions are even, odd, or neither:
1. [tex]\((f \cdot g)(x)\)[/tex]
2. [tex]\((g \cdot g)(x)\)[/tex]
### Step 1: Analyze [tex]\((f \cdot g)(x)\)[/tex]
To determine the nature of the function [tex]\((f \cdot g)(x)\)[/tex], we will consider:
[tex]\[ (f \cdot g)(x) = f(x) \cdot g(x) \][/tex]
For a function [tex]\( h(x) \)[/tex] to be even, it must satisfy:
[tex]\[ h(x) = h(-x) \][/tex]
For a function [tex]\( h(x) \)[/tex] to be odd, it must satisfy:
[tex]\[ h(x) = -h(-x) \][/tex]
#### Check if [tex]\((f \cdot g)(x)\)[/tex] is even:
[tex]\[ (f \cdot g)(-x) = f(-x) \cdot g(-x) \][/tex]
Since [tex]\( f(x) \)[/tex] is even, we know that:
[tex]\[ f(-x) = f(x) \][/tex]
Since [tex]\( g(x) \)[/tex] is odd, we know that:
[tex]\[ g(-x) = -g(x) \][/tex]
Putting these together:
[tex]\[ (f \cdot g)(-x) = f(-x) \cdot g(-x) = f(x) \cdot (-g(x)) = -f(x) \cdot g(x) = -(f \cdot g)(x) \][/tex]
We see that:
[tex]\[ (f \cdot g)(-x) = -(f \cdot g)(x) \][/tex]
This satisfies the definition of an odd function. Therefore,
[tex]\[ (f \cdot g)(x) \text{ is odd} \][/tex]
### Step 2: Analyze [tex]\((g \cdot g)(x)\)[/tex]
To determine the nature of the function [tex]\((g \cdot g)(x)\)[/tex], we will consider:
[tex]\[ (g \cdot g)(x) = g(x) \cdot g(x) = (g(x))^2 \][/tex]
We need to check if this is an even or odd function.
#### Check if [tex]\((g \cdot g)(x)\)[/tex] is even:
[tex]\[ (g \cdot g)(-x) = g(-x) \cdot g(-x) = (g(-x))^2 \][/tex]
Since [tex]\( g(x) \)[/tex] is odd:
[tex]\[ g(-x) = -g(x) \][/tex]
Therefore:
[tex]\[ (g \cdot g)(-x) = (-g(x))^2 = g(x)^2 \][/tex]
We see that:
[tex]\[ (g \cdot g)(-x) = g(x)^2 = (g \cdot g)(x) \][/tex]
This satisfies the definition of an even function. Therefore,
[tex]\[ (g \cdot g)(x) \text{ is even} \][/tex]
### Conclusion:
- [tex]\((f \cdot g)(x) = \)[/tex] neither
- [tex]\((g \cdot g)(x) = \)[/tex] even
Given:
- [tex]\( f(x) \)[/tex] is an even function.
- [tex]\( g(x) \)[/tex] is an odd function.
We need to determine whether the following functions are even, odd, or neither:
1. [tex]\((f \cdot g)(x)\)[/tex]
2. [tex]\((g \cdot g)(x)\)[/tex]
### Step 1: Analyze [tex]\((f \cdot g)(x)\)[/tex]
To determine the nature of the function [tex]\((f \cdot g)(x)\)[/tex], we will consider:
[tex]\[ (f \cdot g)(x) = f(x) \cdot g(x) \][/tex]
For a function [tex]\( h(x) \)[/tex] to be even, it must satisfy:
[tex]\[ h(x) = h(-x) \][/tex]
For a function [tex]\( h(x) \)[/tex] to be odd, it must satisfy:
[tex]\[ h(x) = -h(-x) \][/tex]
#### Check if [tex]\((f \cdot g)(x)\)[/tex] is even:
[tex]\[ (f \cdot g)(-x) = f(-x) \cdot g(-x) \][/tex]
Since [tex]\( f(x) \)[/tex] is even, we know that:
[tex]\[ f(-x) = f(x) \][/tex]
Since [tex]\( g(x) \)[/tex] is odd, we know that:
[tex]\[ g(-x) = -g(x) \][/tex]
Putting these together:
[tex]\[ (f \cdot g)(-x) = f(-x) \cdot g(-x) = f(x) \cdot (-g(x)) = -f(x) \cdot g(x) = -(f \cdot g)(x) \][/tex]
We see that:
[tex]\[ (f \cdot g)(-x) = -(f \cdot g)(x) \][/tex]
This satisfies the definition of an odd function. Therefore,
[tex]\[ (f \cdot g)(x) \text{ is odd} \][/tex]
### Step 2: Analyze [tex]\((g \cdot g)(x)\)[/tex]
To determine the nature of the function [tex]\((g \cdot g)(x)\)[/tex], we will consider:
[tex]\[ (g \cdot g)(x) = g(x) \cdot g(x) = (g(x))^2 \][/tex]
We need to check if this is an even or odd function.
#### Check if [tex]\((g \cdot g)(x)\)[/tex] is even:
[tex]\[ (g \cdot g)(-x) = g(-x) \cdot g(-x) = (g(-x))^2 \][/tex]
Since [tex]\( g(x) \)[/tex] is odd:
[tex]\[ g(-x) = -g(x) \][/tex]
Therefore:
[tex]\[ (g \cdot g)(-x) = (-g(x))^2 = g(x)^2 \][/tex]
We see that:
[tex]\[ (g \cdot g)(-x) = g(x)^2 = (g \cdot g)(x) \][/tex]
This satisfies the definition of an even function. Therefore,
[tex]\[ (g \cdot g)(x) \text{ is even} \][/tex]
### Conclusion:
- [tex]\((f \cdot g)(x) = \)[/tex] neither
- [tex]\((g \cdot g)(x) = \)[/tex] even
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.